Hubungan Higiene Penjamah dengan Keberadaan Bakteri Escherichia coli Pada Minuman Jus Buah di Tembalang - Lestari, Dyah Puji; Nurjazuli, Nurjazuli; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background: Fruit juice is one of a beverages that is easily obtained and become favorite beverages among the students. The making and presentation of beverages with the presence of bacteria contamination in beverages may will be influence by hygiene factors are not qualified. The purpose of this study was to analyze the relation between food handler hyigiene and the existence of Escherichia coli on fruit juice beverages in the Tembalang. Method: This study used observational research  with a cross sectional design. Total samples as many as 25 trader jus, data collection techniques by the laboratory tests and surveys. Data were analyzed using Fisher exact test. Results: The results of the 25 samples showed 13 (52%) fruit juice samples, 11 (44%) samples of boiled water and 14 (56%) samples of water wash containing the bacteria Escherichia coli. There is a relationship between the quality of boiled water with the presence of bacteria E.coli in fruits juice (p=0,001), there is a relationship between the quality of water wash to the presence of bacteria E.coli in fruits juice (p=0,005), there is no relationship between handler hygiene with the presence of  bacteria E.coli in fruits juice (p=0,848), there is no relationship water sanitation with the presence of bacteria E.coli in fruits juice (p=1,000), there is no relationship between  sanitary equipment with the presence of bacteria E.coli in fruits juice (p=0,561), there is no relationship between trash conditions with the presence of bacteria E.coli in fruits juice (p=0,543). Conclusion: This study concluded that  the quality of boiled and washing water as the risk factors of the exixtence of Escherichia coli on fruit juice beverages in Tembalang. Key words: hygiene and sanitation, fruit juice, Escherichia coli.